PEMASARAN PRODUK MENJAHIT PADA PROGRAM PKBM MEKAR SARI - Ida Maeyeni; Agus Zainal Ramat; Ririn Gusti (Jurnal Pendidikan Sepanjang Hayat, 2019)
The objectives of this study were: (1) Knowing the Background of the Sewing Program at PKBM Mekar sari (2) Knowing the Implementation of Sewing Learning at PKBM Mekar Sari (3) Knowing the Marketing of Sewing Products in the Mekar Sari PKBM Program (4) Knowing the Profit and Loss Calculations of Sewing Businesses in PKBM Mekar Sari. Research methods used qualitative methods with descriptive approaches. The participants of the study were Ibuk Titin Sumarni Anjani as Chairman of PKBM Mekar Sari and Simultaneously sewing coach, Ibuk Wulan Widia Astuti as sewing coach, and Siasmawati as sewing coach and Secretary. Dara collection techniques used were non-participant observation, structured interviews, and documentation. To test the validity and reliability of data using triangulation of sources, , techniques, and time. Based on the analysis that has been carried out that the sewing program in PKBM Mekar sari Padang Kedondong Village, Tanjung Kemuning District, , Kaur Regency includes a sewing program. During the implementation of 2x week activities, the coach's role coordinates in the activity, the funds obtained from the Government budget, while the supporting factors of the facility while inhibiting the lack of financial factors.Innovative business carried out by time discipline. Then the supervision is carried out by the trainer directly by observing the activities carried out once every two weeks of training.Keywords: Program, To Sew, PKBM.